Assessing Patient Satisfaction and Service Quality at Svarta Dental Care - Lana aikini (Green Health International Journal of Health Sciences Nursing and Nutrition, 2024)
This study aims to assess patient satisfaction and analyze the quality of dental health services at Svarta Dental Care Bandung clinic. Using a descriptive research design with a sample size of 30 people and accidental sampling, the research instrument was a questionnaire. Data analysis included univariate analysis and Importance Performance Analysis (IPA) using a Cartesian diagram. The results indicated a high level of conformity between reality and expectations across five quality dimensions, emphasizing the need for regular evaluations and improvements in service quality to enhance patient satisfaction.